1974
DOI: 10.1126/science.183.4120.81
|View full text |Cite
|
Sign up to set email alerts
|

α-Ketoglutaramate: Increased Concentrations in the Cerebrospinal Fluid of Patients in Hepatic Coma

Abstract: alpha-Ketoglutaramate, a deaminated metabolite of glutamine not previously identified in biological tissues, was measured in the cerebrospinal fluid of human subjects and found to be increased three- to tenfold in patients with hepatic coma. When perfused into the cerebral lateral ventricles of rats, alpha-ketoglutaramate (10 mM) depressed the animals' nocturnal locomotor activity, and at higher doses induced circling behavior and myoclonus. The concentration of alpha-ketoglutaramate in cerebrospinal fluid app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 21 publications
3
52
0
Order By: Relevance
“…72 Since a significant fraction of glutamine aminotransferase K, a rate limiting enzyme for alpha-ketoglutaramate production is located within the mitochondria, 73 this interesting finding can likewise be reconciled with the Trojan horse hypothesis. A reconsideration of the potential role of alpha-ketoglutaramate in ammonia neurotoxicity is clearly warranted.…”
Section: The Trojan Horsementioning
confidence: 53%
“…72 Since a significant fraction of glutamine aminotransferase K, a rate limiting enzyme for alpha-ketoglutaramate production is located within the mitochondria, 73 this interesting finding can likewise be reconciled with the Trojan horse hypothesis. A reconsideration of the potential role of alpha-ketoglutaramate in ammonia neurotoxicity is clearly warranted.…”
Section: The Trojan Horsementioning
confidence: 53%
“…Increased glutamate concentrations in the cerebrospinal fluid of patients with hepatic encephalopathy suggest that increased extracellular brain glutamate also occurs clinically (Van Sande et al, 1970;Vergara et al, 1974;Watanabe et al, 1984). Increased extracellular glutamate together with a normal NMDA receptor population, might lead to glutamate overexposure.…”
Section: Discussionmentioning
confidence: 99%
“…increased glutamate exposure at the receptor level, during hepatic encephalopathy and hyperammonemia. Increased glutamate concentrations in the cerebrospinal fluid of patients with hepatic encephalopathy suggest that increased glutamate exposure also occurs clinically (Van Sande et al, 1970;Vergara et al, 1974;Watanabe et al, 1984). To explain the paradoxical observation of increased excitatory neurotransmitter molecules in a state of neuroinhibition, the following hypothesis was constructed.…”
Section: Introductionmentioning
confidence: 99%
“…It could also explain why metabolites from ammonia metabolism, such as glutamine and alpha-ketoglutaramate, measured in cerebrospinal fluid from patients with HE seem to correlate better with the severity of HE than blood ammonia. 28 The clinical distinction between hyponatremic encephalopathy and hepatic encephalopathy is a challenge. 29 Recent studies have indicated hyponatremia as an independent risk factor for patients with cirrhosis for developing HE.…”
Section: Discussionmentioning
confidence: 99%